design for Structural Stability - Kirby ([S.l.] : John Wiley & Sons Inc, 1979)
The important influence of instability effects on the design of structural steelwork is becoming generally accepted. This book has been written with the specific aim of presenting the transition from fundamental theories to practical design. The buckling of steel columns, beams and frames is treated in a manner suitable for both the student seeking an introduction to the subject and the more experienced designer requiring explanation of the background to modern.